Dynamic Modeling and Vibration Analysis for the Vehicles with Rigid Wheels Based on Wheel-Terrain Interaction Mechanics - Jianfeng Wang; Yiqun Liu; Liang Ding; Bing Yan; Haibo Gao; Baoyu Song; Tie Gao; Yuzhou Hao; Mingdi Sun (Shock and Vibration)
The contact mechanics for a rigid wheel and deformable terrain are complicated owing to the rigid flexible coupling characteristics. Bekker’s equations are used as the basis to establish the equations of the sinking rolling wheel, to vertical load pressure relationship. Since vehicle movement on the Moon is a complex and on-going problem, the researcher is poised to simplify this problem of vertical loading of the wheel. In this paper, the quarter kinetic models of a manned lunar rover, which are both based on the rigid road and deformable lunar terrain, are used as the simulation models. With these kinetic models, the vibration simulations were conducted. The simulation results indicate that the quarter kinetic model based on the deformable lunar terrain accurately reflects the deformable terrain’s influence on the vibration characteristics of a manned lunar rover. Additionally, with the quarter kinetic model of the deformable terrain, the vibration simulations of a manned lunar rover were conducted, which include a parametric analysis of the wheel parameters, vehicle speed, and suspension parameters. The results show that a manned lunar rover requires a lower damping value and stiffness to achieve better vibration performance.